The Effect of Fluoride Mouthwashes on Orthodontic Appliances’ Corrosion and Mechanical Properties: A Scoping Review - Miltiadis A. Makrygiannakis; Angeliki Anna Gkinosati; Sotirios Kalfas; Eleftherios G. Kaklamanos (Hygiene, 2025)
Fluoride mouthwashes are often recommended by dental professionals due to their proven benefits for oral hygiene. However, it is vital to acknowledge that these products may have undesirable effects on orthodontic treatment outcomes, particularly by altering the biomechanical properties of orthodontic devices and their components. To gain a comprehensive understanding of this potential issue, an extensive and systematic search was conducted across seven distinct databases. PRISMA extension for scoping reviews (PRISMA ScR) guidelines were followed. Following a detailed evaluation and careful scrutiny of the available evidence, a total of seven relevant studies met the inclusion criteria and were incorporated into the current scoping review. Findings indicated that regular intraoral use of fluoride-containing mouthwashes could lead to heightened corrosion and greater release of metal ions from stainless-steel brackets and nickel–titanium (NiTi) archwires. Additionally, the mechanical properties and structural integrity of titanium–molybdenum alloy (TMA) wires were negatively influenced by exposure to fluoride mouthwashes. Although existing evidence highlights these potential drawbacks, there remains a clear necessity for additional comprehensive research. Given the possibility that fluoride mouthwashes could adversely influence orthodontic treatment effectiveness, orthodontists and dental clinicians must exercise cautious judgment and deliberate consideration when prescribing fluoride-based mouthwashes for patients undergoing orthodontic therapy.